GOVERNMENT AND IGNORE RIGHTS FORMAL EDUCATION: CASE STUDY SAMIN COMMUNITY IN KUDUS CENTRAL JAVA - Lina Kushidayati; Moh Rosyid (International Conference on Social and Islamic Studies, 2021)
Samin is Javanese ethnic community originally driven by Ki Samin Surosentiko against invaders in Blora, Central Java. Its existence extends to the city Kudus, Central Java until now. This article describes the character of the Samin community in Kudus against UU as don’t formal and nonformal school and his marriage was registered. This matter violates Education Law and Marriage Law. Data collection by interview, observation, and literature was analyzed using a qualitative descriptive approach. Result, Samin doesn’t register marriage and no formal school. Teachings are held fast by homeschooling to protected generation. This curriculum are not slander (drengki), greedy (srei), hate others (panasten), indict without evidence (dawen), envy (kemeren), contempt fellow (nyiyo marang sepodo), and stay five away from abstinence are accuse (bedok), steal (colong), shoplifting (pethil-jumput); and don’t want to find goods (nemu wae ora keno).Samin community don’t have formal school for maintaining the teachings, inherit the speech in speech, educated by parent and figure, the evaluated in his life. The government must provide understanding so obey UU on an ongoing basis.